Production and Characterization of Scaffold made of Hydroxyapatite and Pectin of Green Cincau Leaf (Premna Oblongifolia Merr) - S Habibie; Y Tristiyanti; D Gustiono; M E Harahap; S Y Chalid; D Effendi (Faculty of Engineering, Universitas Lampung Jl. Soemantri Brojonegoro No.1 Bandar Lampung, Indonesia 35141, 2019)
Scaffold is a 3-dimensional matrix created as a new bone cell growth medium made from natural polymers and bioceramics. The extracted pectin from green Cincau leaves (Premna oblongifolia Merr) and hydroxyapatite (HA) are used in the manufacture of scaffolds. Pectin was extracted using citric acid with variation concentration of 0, 0.1, 0.2 and 0.3% (w / v). The 3% (w / w) HA-pectin mixture, dried freeze using a freeze dryer. The characterization of extracted pectin and HA-pectin scaffold was then performed. The results showed that pectin of green Cincau leaves had low methoxyl content, which was 1.364 to 5.022%. The resulting scaffold has a pore size ranging from 8.25 to 115 µm while the scaffold resistance to the load, i.e. 0.03 to 0.15 MPa. The scaffold porosity that has been made is 15.33 to 40.97% while the density is 0.69 to 1.02 g/cm3